Islam and Deviance in Türkiye - Ozden Ozbay; Sabuha Bindik (UIN Sunan Gunung Djati Bandung, 2023)
The goal of the present study is to explore the link between Islam and deviance using a sample of 1,596 young adults from a public university in Türkiye by employing multivariate statistical analyses. The core independent variables are importance of Islam and political identity (Islamic, nationalist, social democrat/Ataturkist, apolitic, and other). The dependent variables are life-time deviance (an index), cheating on exams, skipping school, cigarette use, alcohol use, carrying a weapon, beating up/hurting someone seriously, and internet crime. The findings indicate that Islam has inverse impacts on various deviant acts, and its effect is stronger for substance use than non-ascetic/secular deviant acts, independent of the control variables (age, gender, monthly total family income, deviant friends, failed courses, high certainty of punishment, high risk seeking, and high maternal control). In other words, importance of Islam is associated negatively with life-time deviance, cheating on exams, skipping school, cigarette use, alcohol use, carrying a weapon, beating up/hurting someone seriously, and internet crime. Islamic political identity, compared to social democratic/Ataturkist political identity, is negatively associated with life-time deviance, cheating on exams, cigarette use, alcohol use, and internet crime. In sum, religion is negatively related with deviant acts.